Desmoplastic Infantile Ganglioglioma: A MAPK Pathway-Driven and Microglia/Macrophage-Rich Neuroepithelial Tumor. Issue 11 (8th October 2019) - Blessing, Melissa M; Blackburn, Patrick R; Krishnan, Chandra; Harrod, Virginia L; Barr Fritcher, Emily G; Zysk, Christopher D; Jackson, Rory A; Milosevic, Dragana; Nair, Asha A; Davila, Jaime I; Balcom, Jessica R; Jenkins, Robert B; et al.
Abstract: MAPK pathway activation has been recurrently observed in desmoplastic infantile ganglioglioma/astrocytoma (DIG/DIA) with reported disproportionally low mutation allele frequencies relative to the apparent high tumor content, suggesting that MAPK pathway alterations may be subclonal. We sought to expand the number of molecularly profiled cases and investigate if tumor cell composition could account for the observed low mutation allele frequencies. Molecular (targeted neuro-oncology next-generation sequencing/RNA sequencing and OncoScan microarray) and immunohistochemical (CD68-PGM1/CD163/CD14/CD11c/lysozyme/CD3/CD20/CD34/PD-L1) studies were performed in 7 DIG. Activating MAPK pathway alterations were identified in 4 (57%) cases: 3 had a BRAF mutation (V600E/V600D/V600_W604delinsDQTDG, at 8%–27% variant allele frequency) and 1 showed a TPM3-NTRK1 fusion. Copy number changes were infrequent and nonrecurrent. All tumors had at least 30% of cells morphologically and immunophenotypically consistent with microglial/macrophage lineage. Two subtotally resected tumors regrew; 1 was re-excised and received adjuvant treatment (chemotherapy/targeted therapy), with clinical response to targeted therapy only. Even with residual tumor, all patients are alive (median follow-up, 83 months; 19–139). This study further supports DIG as another MAPK pathway-driven neuroepithelial tumor, thus expanding potential treatment options for tumors not amenable to surgical cure, and suggests that DIG is a microglia/macrophage-rich neuroepithelial tumor with frequent low driver mutation allele frequencies.